Generic Blurring in Contemporary South African Literary Journalism - (:unkn) unknown (My University, 2023)
This module, taught by Mfuneko Toyana, looked at generic blurring in contemporary South African literary journalism. The first part focused on Chimurenga, one of South Africa’s longest running literary magazines and one of the few spaces available for experimental and literary nonfiction and journalism outside of mainstream book publishing. As a literary magazine using the newspaper format, the Chimurenga actively challenges and distorts the distinction between fiction and nonfiction, while experimenting with genre hybridity and flexibility. The point of this session was to examine how the Chimurenga reimagines and upends the newspaper genre to reflect a real South African experience. The second part of the module, taught by Indiana Lods, looked at Fred Khumalo’s historical novel, The Longest March (2019), about the ten-day, 400-km journey of 7,000 Zulu miners from Johannesburg towards their homes in Natal and Zululand in order to escape the Boer War. Students studied different extracts from the novel (historical background, translations from Zulu to English, descriptions of the landscape, description of a character as a living myth, etc.) as a way to bridge the divide between fiction and nonfiction in South Africa. Supplemental resources included extracts from the interview Indiana Lods conducted with Fred Khumalo, extracts from the history books that the author used to write his novel, and essays and other writings from #ZuptasMustFall and Other Rants (2016), in which the author blends facts, scenes, dialogue and explanations about contemporary South African society.
Keywords: African Research